Statistical handbook on infectious diseases - Watstein, Sarah (Greenwood Press, 2003)
This statistical handbook is designed to offer students, researchers, practitioners, and the general adult population a comprehensive statistical overview of the status of infectious disease worldwide. The availability of this information has increased dramatically on the Internet, yet the data are often too extensive, hard to find, or difficult to interpret. A carefully selected array of tables and charts present authoritative statistical information, placing valuable statistics into context with introductory text.